(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Cardiovascular diseases are the leading causes of death and disability worldwide, and acute coronary syndrome (ACS) is the leading cause. acute coronary syndrome (ACS) is an acute insufficiency of coronary blood circulation based on all clinical manifestations , which usually develops against the background of atherosclerosis of the coronary arteries. The pathomorphological basis of this condition is a violation of the integrity of the atherosclerotic plaque along with its thrombosis . [1 ] Some characteristics of the pathogenesis and clinic of OCD predetermine the most important organizational principles, diagnostic and treatment methods. The principles of treatment are specific when the patient is suspected of OCD, diagnosed diagnostically, or when complications arise. lib, in which time and the chosen treatment algorithm are extremely important and determine the prognosis of the disease and the patient’s future life. This shows that it is important to further improve any stage of treatment of patients with OCD.